Analisis Kinerja Keuangan dengan Menggunakan Rasio Likuiditas, Solvabilitas, dan Profitabilitas Pada PT Semen Indonesia (Persero) Tbk 2024-2025 - Eva Mirandha Nur Cahya; Chinta Syafirna Ramadhani Budi; Andini Dwi Lestari; Eko Edy Susanto (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study is intended to analyze the performance of PT Semen Indonesia (Persero) Tbk financial through liquidity, solvency, and profitability ratios along the 2024–2025 period. The research employed a quantitative descriptive approach using time series analysis based on secondary data obtained from audited annual financial reports. The indicators analyzed were Current Ratio (CR), Quick Ratio (QR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE). The results indicate a decline in the company’s liquidity, as can be seen through the decrease in CR from 1.25 to 1.10 and QR from 0.85 to 0.79. Solvency remained relatively sound despite increases in DAR from 34.60% to 35.46% and DER from 0.55 to 0.57. Meanwhile, profitability experienced a significant decline, with Return on Assets decreasing from 0.93% to 0.25% and Return on Equity from 1.49% to 0.40%. These findings suggest that the company remains competent to fulfill its short- or long-term responsibilities; however, the effectiveness in generating profits has weakened. Therefore, improvements in operational efficiency and asset optimization are necessary to enhance future profit.